Instagram Picture Series to Improve Students Procedure Text - Rahmawati, Vebriary Eka; Musyarofah, Lailatul (English Department, Universitas Negeri Surabaya, 2020)
The research is aimed to know whether the students ability in writing procedure text be improved through the use of Instagram picture series as teaching media. This is a classroom action research (CAR) on the eleventh grade of Madrasah Aliyah NU Sidoarjo in 2018/2019 academic year. The researcher used the CAR model developed by Kemmis and Mc Taggart (1990:14) which includes four steps. They are planning, acting, observing and reflecting. This research used quasi-experimental design. Participants were equally assigned to experiment group and control group. The population is 126 students. The samples are ten students of XI MIPA 1 as the experimental group and ten students of XI MIPA 1 XI MIPA 2 as the control group. The researcher applied two kinds of instrument: writing pre-test and writing post-test. The data was analyzed statistically using T-test. As the result, the percentage growths margin between experimental group and control group is 4.52%. The use of Instagram picture series as teaching media was an appropriate strategy for eleventh grade students of Madrasah Aliyah NU Sidoarjo to improve their ability in writing procedure text. It means that, the use of Instagram picture series as teaching media had the significant positive impact to the improvement of the students ability in writing procedure text.Keywords: instagram picture series, procedure text, improvement, CAR